Epidemiology of Early Monkeypox Virus Transmission in Sexual Networks of Gay and Bisexual Men, England, 2022 - Vusirikala, Amoolya; Charles, Hannah; Balasegaram, Sooria; Macdonald, Neil; Kumar, Deepti; Barker-Burnside, Ceri; Cumiskey, Kerry; Dickinson, Michelle; Watson, Michelle; Olufon, Oluwakemi; Thorley, Katie; Blomquist, Paula; et al. (Emerging infectious diseases, 2022)
After community transmission of monkeypox virus was identified in Europe, interviews of 45 case-patients from England indicated transmission in international sexual networks of gay and bisexual men since April 2022. Interventions targeting sex-on-premises venues, geospatial dating applications, and sexual health services are likely to be critical for outbreak control.